Pengukuran Kinerja Bank Umum Syariah Dengan Maqasid Index Dan Sharia Conformity And Profitability (SCNP) - Lia Anggraeni Prasetyowati; Luqman Hakim Handoko (Jurnal Akuntansi dan Keuangan Islam, 2016)
This study aims to measure the performance of Islamic banking by using maqasid sharia Framework and SCnP model, which both of the models have been adapted to the characteristics of Islamic banking. Research carried out on seven Islamic Commercial Banks (BUS) for five years, from 2010 to 2014. The results by using maqasid index model shows that there are variations and fluctuative performance between BUS. The total of maqasid index over the past five years are in the range from 0,16901 to 0,34297. Bank Muamalat Indonesia is considered as the most stable BUS on maqasid sharia performance during the period of observation. This statement can be concluded from the BMI total index which always exceeds 0,30 and always got the first rank or second rank in each year, except in 2014, where in 2014 a decline of performance simultaneously happened on the 6 samples of BUS including BMI. Next, the performance measurement by using SCnP model, showed that during five years most of the BUS in Indonesia are at LRQ (Lower Right Quadrant) and LLQ (Lower Left Quadrant), it means that most of BUS in Indonesia have high sharia conformity but low profitability, or have low sharia conformity and low profitability. BMI decide as the best performance bank by Using SCnP model. It can be concluded as we know that BMI is the most consistent bank in URQ. Measurement using maqasid index and SCnP model show not only Islamic banks with highest total index can reach URQ. It can be concluded from BPS which two times get the first rank but BPS can not reach URQ.